Vesical calculi in dogs: a radiographic study - Iwasaki, Masao; Sterman, Franklin de Almeida; Crochik, Sonia da Silva (Brazilian Journal of Veterinary Research and Animal Science, 1997)
Forty-three dogs having radiodense calculi were submitted to positive cystography. Disorders that could predispose to the appearance of those calculi were radiographically analysed. In 5 bitches no other anomaly related to calculi was observed. In 34.21% of the 38 remaining dogs calculi were associated to lumbar vertebral osteophytes; 28.95% had vesical diverticula and 15.79% urachal vestige. A large prostate was observed in 15.79% of the dogs, and 5.26% showed lumbar intervertebral disk calcification.